Impact of bone quality on surgical decision-making in total hip arthroplasty: a qualitative analysis in the UK - Stella Mavroveli; Justin Cobb; Sanjeeve Sabharwal; Monil Karia; Alex Abouharb (BMJ Open)
Introduction For total hip arthroplasty (THA) to be successful, surgeons need to make several decisions ranging from implant choice to impaction force. It is unclear, however, whether and how bone quality affects surgeon’s decision-making and how surgeons evaluate bone quality.Objectives This inductive/deductive qualitative hybrid study aims to explore the impact of bone quality on the decision-making of surgeons performing elective primary THA. This study will evaluate: (1) whether surgeons consider bone quality as an important factor for surgical decision-making; (2) how bone quality influences surgical decision-making; and (3) how surgeons assess bone quality preoperatively and intraoperatively.Design This is a qualitative study, involving inductive/deductive hybrid thematic analysis.Setting Semistructured interviews were conducted virtually via Microsoft Teams and on hospital premises.Participants Purposive and snowball sampling methods were used to recruit consultant orthopaedic surgeons specialised in elective lower limb arthroplasty.Results 10 surgeons from eight centres in the UK were interviewed. Thematic saturation was achieved after eight interviews. 5 main themes and 13 subthemes were identified. Bone quality impacted decisions around preoperative planning, surgical procedure, implant choice, concerns of iatrogenic injury and hip biomechanics. Many surgeons (7/10) described changing surgical procedure based on their intraoperative assessment of bone quality. There was consensus that cemented femoral fixation is superior in patients with poor bone quality and on the importance of assessing radiographs preoperatively. There was, however, a lack of consensus on optimal acetabular fixation method, the radiographs metrics used to measure bone quality and attitudes towards current guidelines.Conclusions Bone quality has a significant impact on the decision-making of experienced arthroplasty surgeons, though there are significant limitations and divergence in current methods of assessing bone quality. Further work to identify intraoperative and preoperative imaging metrics that correlate with bone mechanical properties could enhance surgical decision-making.